Bridging the gap between "science" and "security" - Fighel, Jonathan (Array, 2020)
Security is multidimensional in nature and diverse in practice. This diversity leads to difficulty in providing a single all-encompassing definition for the many applied domains of security. Security cannot be considered singular in concept definition, as definition is dependent on applied context. Security incorporates diverse and multi-disciplined actors, originating and practicing across many disciplines. This multidimensional nature of security results unclear understanding of a definition for the concept of security. Bridging the gap between the traditional definitions of science and the undefined definition of what is Security can be achieved through Scientific Security Research methodologies that will be engaged and implemented in the exploration, analysis and conclusions of the systematic and organized body of knowledge.